Selection and evaluation of quality control markers in propolis based on its hyperlipidemia therapy via regulating PXR/CYP3A4 expression - Zhao Chen; Wenhui Luo; Dongmei Sun; Xiaoli Bi; Xiaohui Zeng; Guanlin Xiao; Aili Xu; Weitao Chen; Jieyi Jiang; Xiyuan Li; Lizhong Cao (Elsevier, 2021)
Background: Propolis and its preparations are components of TCM and functional food sources for antihyperlipidemia therapy. However, due to the metabolic properties of propolis, its individual components remain ambiguous, especially those that are therapeutically active. Purpose: The study presented here identified the primary target (PXR/CYP3A4) of propolis activity against hyperlipidemia and evaluated individual compounds of propolis to select a quality control marker based on this activity. Methods: Mice fed a high-fat diet were used to study the efficacy of propolis, followed by identification of substantially influenced glycolipid regulatory target(s) by propolis. Since propolis had the strongest effect on PXR expression, we took advantage of its downstream target CYP3A4, the drug metabolism activity of such enzyme is affected by alterations in PXR expression. Thus, we used the production of 1'-hydroxy-midazolam as an indicator. Compounds found by UHPLC-TOF-MS were added to a HepG2 cell solution (transfected by PXR mRNA and the CYP3A4 plasmid to simulate drug metabolism in the body) in the form of a monomer, followed by the addition of midazolam. Changes in the amount of "indicator" were used to investigate each compound's qualitative (promote or suppress) and quantitative activity. Compounds with obvious effects were quantified in propolis extract, as confirmed via Western Blot analysis regarding their PXR regulatory activity, and subjected to pharmacokinetic analysis to biter understand their metabolism in the body. Finally, components passing these screens could be regarded as quality control markers capable of indicating the efficacy of antihyperlipidemic activity via PXR/CYP3A4 regulation. Results: The use of propolis was effective in lowering TG and TC levels in mice, as well as in repairing their injured livers; its activity was comparable to the chemical and TCM positive controls. Propolis mainly suppressed PXR expression compared with other regulatory targets that were tested. Most of the individual compounds from propolis (13 out of 15) showed obvious regulatory activity of PXR/CYP3A4; however, content quantification and pharmacokinetic analyses narrowed the selection to 2 compounds, kaempferol and chrysin, as the main active components responsible for the antihyperlipidemic effect of propolis. In other words, this study suggested that propolis mainly acts on the PXR/CYP3A4 pathway to regulate glycolipid metabolism, and the 2 compounds mentioned above can be used as quality control markers (QM) to evaluate the efficacy of this activity. Conclusion: Propolis's antihyperlipidemic effect relies on its regulation of PXR/CYP3A4 expression. Kaempferol and chrysin can be regarded as QMs. In addition, the metabolite-based method for evaluating regulatory activity is much faster, more effective, and more reliable than the conventional screening method, paving the way for its future applications.